How the rivals reacted? An empirical analysis on the impact of dividend announcements on the rival firms’ stock valuation - Romero, Frederick P. (Animo Repository, 2017)
Shareholders obtain their returns from capital gain of the stock prices and the income coming from the dividends payments by companies. The investors of the rival companies may choose to change its portfolio and invest in the companies issuing dividends to increase their returns. This study provides inference on the relevance of dividend announcements of the issuing firm on the share value of the industry rivals. The main objective of this paper is to determine if there is an intra-industry effect connected with the dividend issuance of publicly listed companies in the Philippines. Event study methodology was utilized to determine the impact of the corporate event announcements on the market valuation of the rival firms. The study calculates the Cumulative Average Abnormal Returns earned by industry rivals across the −1/+1, −3/+3, −5/+5, −10/+10 and −15/+15 event windows. The level of significance is set at the 90%, 95% and 99% levels using Patell Z (parametric) test, twotailed. The results show that significant negative abnormal price return is evident on Property, Energy, Financials and Materials industries; only the Energy sector did not experience any significant price volatility. The study infers that the investors of the industry rivals view the announcement as a ‘signal’ showing the well-being and future earnings of the issuing firms; transfer of investments from one company to another may result to the negative performance of the industry rivals. © 2017 American Scientific Publishers. All rights reserved.